At the potter"s workshop. Jeremiah 18:1–12: A narrative that reveals more than meets the eye - Wessels, Wilhelm J. (HTS teologiese studies, 2020)
Jeremiah 18:1–12 is a favourite passage often quoted and preached from pulpits. This prose passage however is much more complicated than taken at the face level. A one-dimensional reading misses the intricacies of these verses. The potter scene in verses 1–4 has its first application in verses 5–6 and again in verses 11–12. It is a question how verses 7–10 relate to the other sections in this narrative. The argument presented in this article is that verses 18:7–10 present a different theological viewpoint and serves to clarify what is to be understood what שׁוב in verse 4 implies in real terms. This illustrates that the biblical text is organic and not static, and shows instances of ongoing interpretation within the text itself.Contribution: This article offers original research in the field of biblical studies, more specifically in the field of the Old Testament. This is in line with the scope of HTS Theological Studies. The article aims at indicating that detail textual analysis reveals the complexity of the text tradition we are dealing with.